KARAKTERISTIK EFEK SAMPING KEMOTERAPI PADA PASIEN KANKER GINEKOLOGI DI RSUP PROF. DR. I.G.N.G. NGOERAH - Diwa Santha, I Made Agus; Budiana, I Nyoman Gede; Mulyana, Ryan Saktika; Wijaya Surya, I Gede Ngurah Harry (Essence of Scientific Medical Journal; Vol 22 No 2 (2025): Volume 22 No. 2 (November 2024 - Maret 2025) Essential: Essence of Scientific Medical Journal, 2025)
Introduction: Gynecological cancer is one of the factors contributing to the high mortality rate in women in Indonesia. Gynecological cancer is a group of malignancies that attack the female reproductive organs. One of the treatments for gynecological cancer is chemotherapy. The use of chemotherapy itself certainly has side effects for gynecological cancer patients. Method: his study used a descriptive method with a cross-sectional design. Data were obtained from secondary data in the form of medical records of gynecological cancer chemotherapy patients at Prof. dr. I.G.N.G. Ngoerah Hospital as many as 96 samples that met the inclusion and exclusion criteria. Data analysis used a frequency distribution table. Result: Based on the research results, cervical cancer was found with the highest percentage (50%), the stage with the highest number was stage III (46.9%), and the use of a combination of paclitaxel and carboplatin as the most chemotherapy regimen (88.5%). Side effects of chemotherapy experienced by patients included nausea (91.7%), anemia (83.3%), thrombocytopenia (69.8%), leukopenia (62.5%), diarrhea (53.1%), and vomiting (45.8%). Discussion: It was found that the type of gynecological cancer that was most experienced by patients was cervical cancer with the highest number of stages at stage III. The combination of paclitaxel and carboplatin became the main regimen in gynecological cancer chemotherapy. Side effects experienced by gynecological cancer chemotherapy patients were found to include nausea, anemia, thrombocytopenia, leukopenia, diarrhea, and vomiting. Conclusion: This study concluded that the majority of patients with chemotherapy side effects came with stage III cervical cancer cases and underwent treatment with a combination of paclitaxel and carboplatin. The side effects experienced by patients undergoing chemotherapy were nausea, anemia, thrombocytopenia, leukopenia, diarrhea, and vomiting.